Possibility of metallic cobalt formation in the oxide scale during high-temperature oxidation of Co-27Cr-6Mo alloy in air - Patthranit Wongpromrat; Phacharaphon Tunthawiroon; Eakarach Bumrungthaichaichan; Phisan Ponpo; Thanasak Nilsonthi; Somrerk Chandra-ambhorn; Walairat Chandra-ambhorn (High Temperature Materials and Processes, 2023)
Abstract Co-based alloys are known to be high oxidation-resistant material and used in several high temperature applications. During high temperature oxidation, duplex oxides containing Co and Cr were formed. It was thermodynamically elucidated that when the growing scale was thick enough, the partial pressure of O 2 in the scale dropped. Then, the reduction of CoO occurred for promoting O 2 which was responsible for Cr 2 O 3 production. This work experimentally proved this point by in situ characterising Co-27Cr-6Mo at high temperatures in air by X-ray diffractometer in a grazing incident mode and metallic Co was confirmed to be formed by the reduction of CoO consistent with the image taken and analysed by field emission scanning electron microscope, energy-dispersive X-ray, and electron backscatter diffraction. Furthermore, the change in lattice parameter and the phase transition were observed when the temperature was altered.
Keywords: High-Temperature Coating Behaviors; Nuclear Materials and Properties; Catalytic Processes in Materials Science